2016
DOI: 10.1002/prot.25057
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic disorder accelerates dissociation rather than association

Abstract: The intrinsically disordered protein (IDP) has distinct properties both physically and biologically: it often becomes folded when binding to the target and is frequently involved in signal transduction. The physical property seems to be compatible with the biological property where fast association and dissociation between IDP and the target are required. While fast association has been well studied, fueled by the fly-casting mechanism, the dissociation kinetics has received less attention. We here study how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
2
18
2
Order By: Relevance
“…Previous works have shown that IDPs possess kinetics advantages by virtue of structural flexibility. IDPs show greater binding rates than their ordered counter parts because of higher encounter efficiency, larger capture radius (fly‐casting effect), or reduced orientational restraints . Our observations are different from these results as we are comparing the binding rates for different unfolded proteins (ie, barnase permutants in the unfolded state) rather than between an unfolded protein and its ordered counterpart.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Previous works have shown that IDPs possess kinetics advantages by virtue of structural flexibility. IDPs show greater binding rates than their ordered counter parts because of higher encounter efficiency, larger capture radius (fly‐casting effect), or reduced orientational restraints . Our observations are different from these results as we are comparing the binding rates for different unfolded proteins (ie, barnase permutants in the unfolded state) rather than between an unfolded protein and its ordered counterpart.…”
Section: Discussioncontrasting
confidence: 62%
“…Dynamic signaling processes require a high association rate constant and a high dissociation rate constant for rapid binding/unbinding events and at the same time a sufficient high association constant for specific recognition . It has been found that IDPs possess kinetic advantages over their ordered counter parts as they have higher encounter efficiency, larger capture radius, reduced orientational restraints, or rapid dissociation during the coupled folding‐binding processes . Although the coupled folding‐binding processes of IDPs have been extensively studied, it remains impossible to predict whether an unfolded protein is suitable for molecular signaling via coupled folding‐binding.…”
Section: Introductionmentioning
confidence: 99%
“…These studies generally support the notion that the structures of IDPs bound to their targets accrue sequentially on the latters’ surfaces [4]. Computational studies have sometimes employed simplified representations of proteins and often relied on the structure of the native complex for guidance [1623]. These studies can provide qualitative descriptions of binding mechanisms but typically lack the capability of making quantitative predictions on binding rate constants, though there have been continued developments on the latter front [24, 25].…”
Section: Introductionmentioning
confidence: 78%
“…In terms of the kinetics of interactions, such proteins can have a wide spectrum of association and disassociation rates depending on the mode of interaction (e.g. conformational selection versus induced folding) [65,80,8284]. For a given K d value, the kinetic constants can vary widely [81].…”
Section: Folding Upon Binding Of Idrsmentioning
confidence: 99%